Extension education for industrialising Malaysia: trends, priorities and emerging issues - Md. Sail, Rahim (Universiti Pertanian Malaysia, 1995)
The launching of the Industrial Master Plan (IMP) in 1986 and the success of the New Economic Policy have brought about significant changes in the socioeconomic growth and development of Malaysia. Malaysia's success in the economic field, with an 8% annual growth rate for the past seven years (since 1998) and a considerably low inflation rate of under 4% has placed the country on a solid path to becoming a developed nation in the year 2020. This remarkable achievement presents a pride to all Malaysians as well a challenge to ensure its continuity and even improve the present situation in the year ahead.